Strategic positioning of the organization in its environment (the flexibility approach) - Ogu, Sokari Jusih (Journal of Commerce, Management, and Tourism Studies, 2025)
This study explores the evolving dynamics of resource management, focusing on the relationship between human capital and product value creation. It examines how strategic positioning and resource engineering can enhance efficiency and innovation by treating employees as owners of their human capital. A qualitative approach, including thematic analysis of literature and case studies, was used to evaluate organizational models prioritizing personnel-product synergy, resource allocation, and their impact on value generation. Key metrics analysed included employee engagement, productivity, and product enhancement. The findings reveal a shift from a transactional to a continuum model of resource management, where employees, as dynamic human capital contributors, drive product value beyond intrinsic levels. Strategic positioning plays a crucial role, involving the reallocation of resources to functional variables. This dynamic process, termed "resource engineering", fosters innovation by aligning human energy with organizational goals. The study emphasizes the need for a visionary approach in resource management, where employers plan and implement strategies that create sustainable value. It also underscores the importance of synergizing human capital for enhanced product value and competitive advantage. Future research should explore practical applications of resource engineering across various industries to validate these findings.